2017
DOI: 10.3126/jcmc.v6i3.16699
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial problems among the school children of working and non- working mothers

Abstract: Adolescence is the period in human development during which several dramatic changes at biological, social, psychological and cognitive levels take place. The objective of this study was to find out psychosocial problems among school children of working and non-working mothers. A descriptive comparative research design and Probability Stratified Random sampling technique was applied in which 120 (60 working and 60 non working mothers') school students of grade 9 and 10 selected from two Government Higher Secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…A previous cross-sectional study in Hetauda, Nepal, showed that 134 (17.03%) were suffering from psychosocial problem [ 11 ]. Another descriptive comparative study in Bharatpur also revealed that school children of nonworking mothers 11.7% had slightly more psychosocial problems than working mothers 8.3% [ 15 ]. A similar finding revealed a cross-sectional study in Pune which showed that 328 (15.2%) children were found to be at risk of psychosocial problems [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous cross-sectional study in Hetauda, Nepal, showed that 134 (17.03%) were suffering from psychosocial problem [ 11 ]. Another descriptive comparative study in Bharatpur also revealed that school children of nonworking mothers 11.7% had slightly more psychosocial problems than working mothers 8.3% [ 15 ]. A similar finding revealed a cross-sectional study in Pune which showed that 328 (15.2%) children were found to be at risk of psychosocial problems [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Findings of previous descriptive comparative study in Bharatpur showed that internalizing problems were found equal (13.3%) in children of working and nonworking mothers whereas attention problems were slightly higher in the school children of working mothers (11.7%) than school children of nonworking mothers (10.0%). Externalizing problems were found slightly higher in the respondents of nonworking mothers (8.3%) than children of working mothers (5.0%) [ 15 ]. Findings of another study in urban and rural areas of Dehradun showed that anxiety and conduct disorders were more common among adolescents in rural area (11.0% and 13.0%, respectively) while depression was more common among adolescents in urban area (26.0%) [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have found that 33.3% of adolescents had psychosocial problems. Several studies from Nepal and India found psychosocial problems among 15-41% of adolescents [4,7,[12][13][14][15]. Such findings suggest a vulnerability of this population to mental health problem and a need for robust school-based mental health programs.…”
Section: Mental Health Status Of Adolescentsmentioning
confidence: 99%
“…4,5 Some adolescents are particularly vulnerable to poor health and developmental outcomes as a result of individual and environmental factors. 6 Various Studies conducted in different parts of the world shows that prevalence of psychosocial problems among adolescents' ranges from 12% to 45%. 3,4,[7][8][9][10][11][12][13][14][15] There are very limited studies conducted in similar settings on psychosocial problems in Dang and detecting these in the early adolescence can be fruitful for the quality of life of the individual.…”
Section: Introductionmentioning
confidence: 99%